Selection of Ceiling Fans for the Microclimate System of Livestock Facilities - A. V. Kuzmichev; D. A. Tikhomirov; A. V. Khimenko (Сельскохозяйственные машины и технологии, 2025)
A literature review revealed that the distribution of air flows and indoor temperatures is influenced by several key factors; including building design; external climatic conditions; internal heat sources; and ventilation system operation. It was demonstrated that livestock buildings exhibit a temperature gradient along the room height; which can reach 6 degrees Celsius or more. An assessment of potential air temperature variations at different heights across various types of livestock facilities was conducted. It has been found that the use of ceiling fans enables a more uniform distribution of air; ensures the standard airflow velocity in the working area; and helps to reduce the concentration of harmful gases and microorganisms in animal zones. (Research purpose) The study aims to develop recommendations for selecting ceiling fans in agricultural premises to equalize air temperature at different heights and ensure uniform distribution of supply air; while maintaining regulated air flow velocity in animal housing areas. (Materials and methods) Various approaches and models for describing the propagation of compact jets and supply air jets from axial ceiling fans were analyzed. (Results and discussion) The range of possible variations in the ceiling fan performance was determined ensuring the normative air velocity in the animal zone; depending on suspension height and blade diameter. General analytical expressions were presented for modeling the propagation of both free and confined compact air jets. Additionally; the behavior of confined compact air jets in buildings with typical height characteristics was analyzed. (Conclusions) The obtained analytical expression defines the relationship between ceiling fan parameters and air flow characteristics; considering the regulated air flow velocity in the working zone. Calculated dependencies and recommendations were provided for determining the optimal number of ceiling fans needed to equalize the air temperature along the room height.